Biological activity and genome composition of a Tunisian isolate of Spodoptera littoralis nucleopolyhedrovirus (SpliNPV-Tun2) - Saoussen Ben Tiba; Asma Laarif; Jörg T. Wennmann; Thameur Bouslama; Johannes A. Jehle (Egyptian Journal of Biological Pest Control, 2022)
Abstract Background The baculovirus Spodoptera littoralis nucleopolyhedrovirus (SpliNPV) is an entomopathogenic virus utilized as a biological control agent of the Egyptian cotton leaf worm, Spodoptera littoralis. Several studies have focused on the identification of different SpliNPV isolates from a biological and molecular point of view, but few of them conducted in-depth analyses of the genomic composition of these isolates. Results Identification of a novel isolate of SpliNPV, termed Tun2, which was purified from infected S. littoralis larvae from Tunisia was reported. This isolate was propagated in vivo and its median lethal concentration (LC50) was determined to be 1.5 × 104 occlusion bodies (OBs)/ml for third instar S. littoralis larvae at 7 days of post-infection. OB production in late fourth instar larvae was estimated to be at least 2.7 × 109 OBs/g larval weight. The completely sequenced genome of SpliNPV-Tun2 was 137,099 bp in length and contained 132 open reading frames (ORF). It showed a 98.2% nucleotide identity to the Egyptian isolate SpliMNPV-AN1956, with some striking differences; between both genomes, insertion and deletion mutations were noticed in 9 baculovirus core genes, and also in the highly conserved polyhedrin gene. The homologs of ORF 106 and ORF 107 of SpliNPV-AN1956 appeared to be fused to a single ORF 106 in SpliNPV-Tun2, similar to the homologous ORF 110 in SpltNPV-G2. Conclusion SpliNPV-Tun2 is proposed as a new variant of SpliNPV and a potential candidate for further evaluation as a biocontrol agent for S. littoralis and probably other Spodoptera species.